Executive functions as predictors of syntactic awareness in English monolingual and English–Spanish bilingual language brokers and nonbrokers. (1st September 2015) - RAINEY, VANESSA R.; DAVIDSON, DENISE; LI-GRINING, CHRISTINE
ABSTRACT: Executive function (EF) skills (cognitive flexibility, inhibition, and working memory) and syntactic awareness of monolingual (English) and bilingual (English–Spanish) language brokers and nonbrokers were examined. EF skills may be salient for brokers, who must not only inhibit interference from another language but also exhibit EF skills when translating. The brokers displayed better cognitive flexibility when compared to the other groups. For the bilingual groups, cognitive flexibility was also a predictor of English syntactic awareness when accuracy was taken into account. Cognitive flexibility and inhibition were important factors on a Spanish syntactic awareness measure. These results are discussed in terms of how linkages between EF skills and syntactic awareness may be moderated by language group.